ALGORITHM FOR SELECTING A FLOW METER WITH OPTIMAL PARAMETERS - Allahverdiyev, Elsevar Nabi (Technologies and Engineering, 2022)
Problems. In many cases, the problem arises of choosing from a variety of alternatives to measuring instruments necessary for measuring the parameters of a technological process. So as that measuring instruments with different designs, operating principles and different technical and technological parameters are produced by different manufacturers. One of the important problems in the development of these systems is the selection of measuring instruments with optimal operational and metrological characteristics in accordance with the manufacturer's specifications and the terms of reference for the system design. Methodology. Multiple criteria decision-making (MCDM) are used in order to solve problems related to several criteria. The high accuracy sensors ensure accurate readings, although there are several parameters involved in measuring process: flow rate; gas or gases used; temperature; operating pressure; pressure drop; price; accuracy; response time; warm-up time; stable measurement range (turndown) gas is selected. Findings. Selection process of the optimal gas flow meter for information-measuring system is considered. Criteria for selection of the flow meters is studied, shown that the selection process is multi-criterial problem. Algorithm for selection of the gas flow meter is proposed. Proposed algorithm based on AHP method and TOPSIS. An idea of algorithm is following. İnitially experts select some alternatives, which meet all requirements for flow meters of different suppliers. At the next step the relative criteria of importance are calculated. After that decision matrixes are composed by which determine the preferences for the goals. Originality. Better alternative or flow meter with optimal parameters is determined by ranking of all alternatives. Practical value. Applying of the proposed algorithm increases reliability of the final decision and automates the selection process by using of the corresponding software.